“We, as Parents, Do Have a Voice”: Learning from Community-Based Programs Effectively Engaging Parents in Urban Communities - Gil, Elizabeth; Johnson, Ashley (Urban education (Beverly Hills, Calif.), 2024)
Utilizing Yosso’s community cultural wealth framework as a theoretical lens, we sought to examine how nontraditional, community-based family engagement programs impacted adult family members’ thoughts and actions about engagement with their children's schools. The study drew primarily from the interviews, observations, and document analysis of two nontraditional family engagement programs in urban communities. Findings indicate that program approaches built upon and extended families’ social and navigational capitals. Educational leaders can more meaningfully engage urban families by learning from and incorporating practices implemented by the programs we examine and discuss in this article.